2018
DOI: 10.32394/rpzh.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment to lead, cadmium, zinc and copper released from ceramic and glass wares intended to come into contact with food

Abstract: Background. One of the important source of food contamination with elements harmful to human health such as lead or cadmium is migration from the articles intended to come into contact with food. Ceramic and glass articles can also be a source of zinc and copper which compounds are used during the production process of vessels. Objective. Determination of migration of lead, cadmium, zinc and copper from ceramic and glass wares available on the market in Poland and assessment of consumer exposure to these eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It may be observed that arsenosugars are accumulated in marine algae and crustaceans at high concentrations of up to 100 mg kg −1 . [83][84][85] AsB, an amino acid derivative, is predominant in most nsh and shellsh, zooplankton, and some algae, while arsenolipids are present in seaweeds.…”
Section: Biota Accumulationmentioning
confidence: 99%
“…It may be observed that arsenosugars are accumulated in marine algae and crustaceans at high concentrations of up to 100 mg kg −1 . [83][84][85] AsB, an amino acid derivative, is predominant in most nsh and shellsh, zooplankton, and some algae, while arsenolipids are present in seaweeds.…”
Section: Biota Accumulationmentioning
confidence: 99%
“…Methylmercury contaminations are constantly increasing in the environment due to human activities, such as metal mining and coal power plants, which release more than one thousand tons of mercury per year . Moreover, its huge biomagnification along the food chain results in significant accumulation of mercury in aquatic species, with consequent potential risks to human health, due to consumption of contaminated food, in particular shellfish and large‐size fish. As a consequence, international authorities have fixed rigid limits for organic mercury concentration in food (500–1000 ppb) .…”
Section: Figurementioning
confidence: 99%
“…So far, the toxicity of heavy metal ions, like Cd 2+ and Cu 2+ , are being paid more and more attentions, as they are nondegradable and inevitably released from human activities like mining, smelting, and manufacturing [1][2][3][4]. Free Cd 2+ and Cu 2+ have been found to be toxic to rat, mice, and various fishes; causing weight loss, developmental abnormality, and even death [5][6][7].…”
Section: Introductionmentioning
confidence: 99%